SWAT Check: A Screening Tool to Assist Users in the Identification of Potential Model Application Problems. Issue 1 (1st January 2014) - White, Michael J.; Harmel, R. Daren; Arnold, Jeff G.; Williams, Jimmy R.
Abstract : The Soil and Water Assessment Tool (SWAT) is a basin‐scale hydrologic model developed by the United States Department of Agriculture Agricultural Research Service. SWAT's broad applicability, user‐friendly model interfaces, and automatic calibration software have led to a rapid increase in the number of new users. These advancements also allow less experienced users to conduct SWAT modeling applications. In particular, the use of automated calibration software may produce simulated values that appear appropriate because they adequately mimic measured data used in calibration and validation. Autocalibrated model applications (and often those of unexperienced modelers) may contain input data errors and inappropriate parameter adjustments not readily identified by users or the autocalibration software. The objective of this research was to develop a program to assist users in the identification of potential model application problems. The resulting "SWAT Check" is a stand‐alone Microsoft Windows program that (i) reads selected SWAT output and alerts users of values outside the typical range; (ii) creates process‐based figures for visualization of the appropriateness of output values, including important outputs that are commonly ignored; and (iii) detects and alerts users of common model application errors. By alerting users to potential model application problems, this software should assist the SWAT community in developing more reliable modeling applications.